Criminal Liability In The Crime Of Corruption In The Construction Of A 4G Base Transceiver Station (Bts) - Herli Antoni; Mustakim; Lilik Prihatini; Asmak Ul Hosnah; Walter AL Sinaga (PALAR | PAKUAN LAW REVIEW, 2026)
This writing aims to find out the factors that cause corruption, criminal liability in the corruption act of the construction of the 4G Base Transceiver Station (BTS) carried out by the President Director of Bakti in Perkaran Decision Number 3/Pid.Sus-TPK/2024/PT DKI. This writing uses a normative legal writing method with a legislative and case approach. The legal materials used are primary and secondary legal materials and are analyzed using prescriptive-normative analysis. The results of the writing show that: (1) Abuse of Authority influenced by the organizational structure of the Ministry of Communication and Informatics which places Bakti under and responsible to the Minister through the Secretary General. The authority of the President Director of Bakti to be fully accountable to the Minister is very ineffective. (2) The lack of technical supervision is also the cause of corruption in the construction of 4G BTS. Supervision is technically impossible for the Secretary General because the duties and functions of the Secretary General are more about providing administrative support to all organizational elements within the Ministry. (3) Another factor is that political pressure or political intervention in the procurement of projects can create opportunities for acts of corruption. Criminal liability in the crime of corruption in development is in the form of imprisonment for eighteen years and a fine of one billion rupiah and an additional penalty in the form of payment of five billion rupiah in lieu of money, but the verdict or punishment imposed by the judge is still too light, which is feared that it cannot have a deterrent effect on the perpetrator in accordance with the purpose of the crime. Keywords: Accountability, Corruption, Base Transceiver Station construction